High throughput method for simultaneous screening of membrane permeability and toxicity for discovery of new cryoprotective agents - Nima Ahmadkhani; James D. Benson; Ali Eroglu; Adam Z. Higgins (Scientific Reports)
Abstract Cryoprotective agent (CPA) toxicity is the most limiting factor impeding cryopreservation of critically needed tissues and organs for transplantation and medical research. This limitation is in part due to the challenge of rapidly screening compounds to identify candidate molecules that are highly membrane permeable and non-toxic at high concentrations. Such a combination would facilitate rapid CPA permeation throughout the sample, enabling ice-free cryopreservation with minimal toxicity. This study presents a new method for rapidly assessing the cell membrane permeability and toxicity of candidate CPAs. The new method enables ~ 100 times faster permeability measurement than previous methods, while also allowing assessment of CPA toxicity using the same 96-well plate. We tested five commonly used CPAs and 22 less common ones at both 4 °C and room temperature, with 23 of them passing the screening process based on their favorable toxicity and permeability properties. Considering its advantages such as high throughput measurement of membrane permeability along with simultaneous toxicity assessment, the presented method holds promise as an effective initial screening tool to identify new CPAs for cryopreservation.